Induction and glucose repression of xylanase from a color variant strain of Aureobasidium pullulans - Leathers, T.D; Detroy, R.W; Bothast, R.J (Biotechnology letters, 1986)
Xylose, Xylobiose and arabinose were identified as natural and direct inducers of xylanase from a color variant strain of Aureobasidium pullulans . Arabinose, in contrast to xylose, xylobiose and xylan, induced only the major isozyme of xylanase. Xylanase induction was subject to glucose repression.